Practices of Price Adjustment in Selected Construction Projects - Pokharel, Sagar; Marasini, Megh Raj (Journal of Lumbini Engineering College, 2022)
Price adjustment affects all the stakeholders i.e. client, consultant and contractor. This research reveals the trend of the cost of components of construction i.e. labor, material, fuel, equipment etc., compare the different formulas of price adjustment and understand the view of client, consultant and contractor regarding price adjustment. Ten contracts commencing within 2010 A.D to 2019 A.D have been chosen. The four contracts have used FIDIC formula, five have used PPMO formula and one has used small works formula. Trend of cost of labor, bitumen, fuel has been analyzed for contracts using FIDIC formula and the trend of NRB index of labor, material and equipment has been analyzed for contracts using PPMO formula. The formula used in the contracts have been compared with other formulas under same circumstance that original formula was used. Questionnaire was distributed to the client, contractor and consultant’s representative. On Contracts using FIDIC formula, the cost of labor can be predicted to increase in future. The cost of fuel and bitumen cannot be predicted as it is fluctuating with respect to time. Comparing the price adjustment factor using different formulas, it cannot be generalized that which formula could give minimum value of price adjustment.